Lithium trapping in alloy forming electrodes and current collectors for lithium based batteries. Issue 6 (11th May 2017) - Rehnlund, David; Lindgren, Fredrik; Böhme, Solveig; Nordh, Tim; Zou, Yiming; Pettersson, Jean; Bexell, Ulf; Boman, Mats; Edström, Kristina; Nyholm, Leif
Abstract : Significant capacity losses due to lithium trapping are demonstrated for lithium alloy forming anode materials such as silicon and tin. Abstract : Significant capacity losses are generally seen for batteries containing high-capacity lithium alloy forming anode materials such as silicon, tin and aluminium. These losses are generally ascribed to a combination of volume expansion effects and irreversible electrolyte reduction reactions. Here, it is shown, based on e.g. elemental analyses of cycled electrodes, that the capacity losses for tin nanorod and silicon composite electrodes in fact involve diffusion controlled trapping of lithium in the electrodes. While an analogous effect is also demonstrated for copper, nickel and titanium current collectors, boron-doped diamond is shown to function as an effective lithium diffusion barrier. The present findings indicate that the durability of lithium based batteries can be improved significantly via proper electrode design or regeneration of the used electrodes.